Integrating Morowali Local Wisdom into Multiliteracy Pedagogy: An Intervention Study on Elementary Descriptive Writing - Putry Damayanti; Syamsuddin Syamsuddin; Yunidar Yunidar (Journal of Innovation and Research in Primary Education, 2026)
Elementary students frequently struggle with descriptive text writing due to decontextualized instruction disconnected from their cultural experiences. This study examined the effectiveness of a multiliteracy approach infused with local wisdom on fifth-grade students' descriptive writing abilities. A quasi-experimental design with nonequivalent control groups was employed, involving 25 fifth-grade students at SDN 2 Bungku, Morowali Regency, Indonesia. The experimental group (n=13) received multiliteracy instruction integrated with Morowali local wisdom, while the control group (n=12) received multiliteracy instruction without cultural contextualization. Descriptive writing ability was assessed using a validated analytical rubric (α=0.87) encompassing content, organization, vocabulary, language use, and mechanics. Data were analyzed using independent samples t-test and Cohen's d effect size. The experimental group achieved significantly higher posttest scores (M=84.16, SD=3.98) compared to the control group (M=72.96, SD=4.29), t(48)=-10.54, p<0.001. Cohen's d of 2.71 indicated an exceptionally large treatment effect. Integrating local wisdom into multiliteracy pedagogy creates synergistic benefits by providing culturally familiar contexts that facilitate idea generation and reduce cognitive load, enabling students to leverage experiential knowledge as compositional resources. Local wisdom-infused multiliteracy approaches substantially enhance elementary students' descriptive writing abilities, offering a culturally responsive pedagogical framework for Indonesian language instruction.